The Stress Level of Elderly who Lives with Family at Home and at Nursing Home - Dyah Widodo; Ganif Djuwadi (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2021)
Elderly is the last stage of human life. Adaptation to loss and limitations in old age is influenced by previous personalities. The presence of people closest to the elderly can affect the level of stress and feelings of worthlessness that lead to depression. The objectives of the study analyzed the differences stress levels in the elderly who received social support from family at home and from peers in the nursing home. The design of the study was comparative study. The population was the elderly who live in nursing home and who live with their families in East Java.  The sample was 60 people, divided into 2 (two) groups, each group was 30 people taken by purposive samples. The stdy was done on Malang Raya and Tresna Werdha Social Service Pandaan nursing home (East Java). The study was conducted in 2018. The instruments study used questionnaires. The data analysis used independent sample t-test. The results showed that there was no difference in the psychological condition stress level of the elderly who received social support from family at home and from peers in the nursing home with Alpha value 0.053 greater than alpha 0.05. It is expected that families and managers of the nursing home to provide good support to the elderly so that the elderly avoid the stress.